2018
DOI: 10.1111/jace.15542
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric properties of (Na0.5K0.5)(Nb1‐xSbx)O3‐SrTiO3 ceramics with tetragonal‐pseudocubic PPB structure

Abstract: CuO‐added 0.96(Na0.5K0.5)(Nb1‐xSbx)O3‐0.04SrTiO3 ceramics sintered at the low temperature of 960°C for 10 hours showed dense microstructures and high relative densities. The specimens with 0.0 ≤  x ≤ 0.04 had orthorhombic‐tetragonal polymorphic phase boundary (PPB) structure. Tetragonal‐pseudocubic PPB structure was observed in specimens with 0.05 ≤  x ≤ 0.07, while the specimen with x = 0.08 has a pseudocubic structure. The structural variation in the specimens is explained by the decreases in the orthorhombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
(208 reference statements)
0
5
0
Order By: Relevance
“…Moreover, a pseudocubic (PC) structure was observed at temperatures near T C [ 77 , 78 , 79 ]. The PC structure cannot be considered as a cubic (C) structure because a KNN-modified ceramic with a pure PC structure exhibits piezoelectric properties [ 80 ]. Therefore, a PC structure was interpreted as an R structure or the T–C multistructure based on Rietveld analysis [ 77 , 78 , 79 , 80 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, a pseudocubic (PC) structure was observed at temperatures near T C [ 77 , 78 , 79 ]. The PC structure cannot be considered as a cubic (C) structure because a KNN-modified ceramic with a pure PC structure exhibits piezoelectric properties [ 80 ]. Therefore, a PC structure was interpreted as an R structure or the T–C multistructure based on Rietveld analysis [ 77 , 78 , 79 , 80 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PC structure cannot be considered as a cubic (C) structure because a KNN-modified ceramic with a pure PC structure exhibits piezoelectric properties [ 80 ]. Therefore, a PC structure was interpreted as an R structure or the T–C multistructure based on Rietveld analysis [ 77 , 78 , 79 , 80 ]. In addition, the PC structure has been understood as various structures depending on the specimens in which the PC structure is developed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21] In addition, KNN is a ferroelectric material with a higher Curie temperature, which can effectively improve temperature stability. [22,23] Chai et al [24] reported that KNN, as a transparent ferroelectric material, can effectively improve the energy storage density, so it is feasible for KNN ceramics to be used in pulse capacitors.…”
Section: Introductionmentioning
confidence: 99%